A sample of an integrated curriculum for grade five. (c2004) - Harati, Lina (2004)
I would like to thank the following people for their effort and support in the accomplishment of this degree. First, to God who gave me the energy and encouragement throughout these years. My parents, Laila, and Mel hem were of great support and help, I truly express my gratitude. It is important to note that my professors were of extreme help and a great source of encouragement. Dr. Bahous, you are not only my professor and role model but also my guardian angel, I am really grateful for everything. Dr. Majdalani, I truly express my thanks to you for trusting and encouraging me, if it was not for you I would never have done it. I would also like to thank my friends who were always there when I needed a hand. Rana Ramia, we went through a lot together, and you were my great editor throughout the years. Nisreen Zaatari, Zeina Osseiran, I am grateful that you believed in me and always had a smile on your taces. Suha Karaky, I really appreciate your encouragement and help. Louma Saddick, Maya Abou Teen, and Lina Shami, thank you for helping me out. Mr. Jaroudi you were of extreme help 1 really thank and appreciate what you have done to me all through these years. Last but not least, I would like to thank Dr. Harb, Dr. Osta, Dr. Nabhani, Dr. Oueini, Dr. Haraty. Ms. Haraty, Dr. Nawas, Dr. Faour and all the professors and staff at the Lebanese American University who assisted me with a great smile since the day I entered this institution.